Stability of carotenoid composition in orange sweet potato (Ipomoea batatas) tuber flesh over three growing seasons and 6 months storage time - Othman, Rashidi; Kammona, Suhair; Jaswir, Irwandi; Jamal, Parveen; Mohd Hatta, Farah Ayuni (Lifescience Global, 2017)
Considerable research interest has recently focused on the development of both transgenic and traditional breeding methods to increase total and individual carotenoid composition in sweet potatoes. Unfortunately little information is available on the influence of the environment on carotenoid profile stability in sweet potatoes especially growing seasons and storage. Therefore the aim of this study is to explore the composition and concentration of carotenoids in orange sweet potato tubers to enable their future enhancement through genetic manipulation over different growing seasons and storage time. Our findings revealed that orange sweet potato tubers contained α-carotene and β-carotene in the first and second season, whereas in the third season only lutein and zeaxanthin were detected. Analysis of carotenoid profiles of the orange sweet potato tubers grown in three different seasons showed that the growing season had a major effect on the carotenoid compounds stability. Besides growing seasons, the level of total and individual carotenoids in orange sweet potato tuber flesh are strongly influenced and affected by storage conditions. The storage of tubers over 6 months period of time appears to have distinct effects on carotenoid content and composition. Results showed that storage from 1 to 6 months resulted in the accumulation of zeaxanthin and β-carotene with a concomitant decreased of lutein, α-carotene and total carotenoid content.